Biosynthesis of high molecular weight dextrans by inoculation with Leuconostoc mesenteroides, var. mesenteroides (ATCC 10830) residual juice from pineapple agroindustry: synthesis and characterization of iron-dextrans (INNOTEC, 2013)
In this work we report studies for dextrans from pineapple agroindustrial-wastes. Fermentation was carried out in a bioreactor (10 L) where the juice was inoculated with a culture of Leuconostoc mesenteroides, var. mesenteroides (ATCC 10830). It was centrifuged, and precipitated and purified with ethanol. It was characterized by viscosity, molecular weight and functional groups by infrared spectroscopy. This dextran was treated to obtain iron-dextran.
Keywords: Polymer; dextran; iron-dextran